Nimble Cloning: A Simple, Versatile, and Efficient System for Standardized Molecular Cloning - Yan, Pu; Zeng, Yanjing; Shen, Wentao; Tuo, Decai; Li, Xiaoying; Zhou, Peng (Frontiers in Bioengineering and Biotechnology, 2020)
Molecular cloning is one of the most fundamental technologies in molecular biology, and has been critical for driving biotechnological advances. In this study, we have developed a novel method for standardized molecular cloning. The cloning technique known as “Nimble Cloning” uses the restriction enzyme, SfiI, in combination with the T5 exonuclease, to linearize the vector and generate 3′-overhangs simultaneously. Both PCR products and plasmids can be used for the cloning reaction in the Nimble Cloning system. The cloning system is highly efficient, suitable for gene expression in both prokaryotic and eukaryotic expression systems, and enables the reuse of DNA fragments or plasmid entry clones. Nimble Cloning is applicable for the cloning of single or multiple fragments, as well as multi-site cloning. Due also to its simplicity and versatility, the cloning method has great potential for the modular assembly of DNA constructs.